The geography of grassland plant chemistry and productivity accounts for ant sodium and sugar usage. Issue 2 (9th February 2020) - Clay, Natalie A.
Abstract: In Focus: Kaspari, M., Welti, E. A. R., & de Beurs, K. M. (2020). The nutritional geography of ants: Gradients of sodium and sugar limitation across North American grasslands. Journal of Animal Ecology, 89, 276‐284. Biologically essential elements and macromolecules impact individuals to ecosystems and vary across space. Predictive frameworks for understanding community patterns across nutritional gradients are increasingly important as the nutritional landscape is continually altered by global change. Grasslands vary in the quantity and quality of essential nutrients that can impact plant consumer abundance, biomass and activity, but causes for variation, particularly across large spatial scales are poorly understood. In 53 North American grasslands spanning 16° latitude, Kaspari et al. (2020) tested three hypotheses for explaining sources of sodium (Na) limitation and five hypotheses for explaining sources of sugar limitation of ants, which are common and ecologically important omnivores that consume both plant‐ and animal‐derived material. For both Na and sugar, over half of the variation in ant bait usage was accounted for by their predictions. Specifically, after accounting for ant activity (ant usage of sugar baits), ant Na‐limitation was next best predicted by plant Na content and lastly, insect biomass, while sugar limitation after accounting for activity (ant usage of Na baits) was best predicted by growing season, then ecosystem productivity, plant potassium (K) and phosphorous (P), respectively. Kaspari et al. (2020) demonstrate the importance of plant physiology and chemistry towards a predictive framework for understanding sugar‐ and Na‐limitation and highlights the importance of tackling ecological questions from a geographical perspective. This framework can provide a useful foundation for predicting future patterns in grassland organism nutritional ecology as plant species and physiology are altered with global change. Abstract : Kaspari et al. (2020) builds toward a nutritional geography and predictive framework for understanding community ecology. They novelly explore potential drivers of sugar geography and generate a new hypothesis that plants can provide substantial sodium for omnivores, which challenges current dogma that sodium is non‐essential for plants, which are sodium‐poor.